Effect of Deferent Type of Training on C-reactive protein Level in Healthy Middle Age Men - Al Hindawi, Mohammad; Mjallie, Majed (European Scientific Journal, ESJ, 2016)
Objective: The goal of our study was to investigate the effect of different type of exercise training on C-reactive protein level in middle age men. Methods: A total of 20 male subjects’ mean age 45±5 years were investigated at the University of Jordan Hospital to evaluate CRP level after training. Subjects were divided randomly into two groups they participated in supervise exercise training resistance and endurance exercise for 11 weeks. CRP level was measured pre-post training. Results: Mean C-reactive protein level measured before training program was 1.82 mg/L. And 1.81 mg/L for endurance and resistance groups respectively. Measurement of the CRP after the completion of the exercise program was 1.654 mg/L and 1.764 mg/L for both groups the endurance and the resistance respectively. TC was significantly reduced from 199.1 ml/dl to 176.1 ml/dl, for the endurance group and from 193.50 ml/dl to 181.60 ml/dl, for the resistance group. TG reduced significantly from 172.2 ml/dl to 161.50 ml/dl for the endurance group, and from 163.50 ml/dl to 159.20 ml/dl for the resistance group. HR at rest reduced from 79.63 b.pm to 74.47 b.pm for the endurance group, and from 77.50 b.pm to 74.6 b.pm for the resistance group. Fat % reduced significantly from 25.25 to 23.22 for the endurance group and from 23.03 to 21.60 for the resistance group. BMI reduced from 28.82 to 27.41 for the endurance group and from 27.63 to 27.40 for the resistance group.VO2max increased significantly from 37.13 to 43.30 ml.kg.min for the endurance group, and from 37.67 to 39.3 for the resistance group. HDL also increased from 46.12 mi/dl to 48.25 mi/dl for the endurance group, and increased from 42.70 mi/dl to 44.30 mi/dl for the resistance group Training gropes had lower CRP, weight, BMI, and body fat after the completion of the exercise program. Conclusions: Plasma C-reactive protein levels are reduced in response to both strength and endurance exercise training in sedentary healthy men (there was no different in the type of exercise in reducing CRP level.